2018
DOI: 10.22161/ijels.3.6.33
|View full text |Cite
|
Sign up to set email alerts
|

Improving Positive Learner Motivation towards Islamic Studies

Abstract: The success in Islamic studies is getting lower and lower, and many learners are having difficulties with learning Islamic studies and with that also the motivation for learning Islamic studies decreases. The difficulties are shown in both, mastering the material in school and solving the exercises at home. For this reason, the study aims to improve positive learner motivation in learning Islamic studies. The aim of this study is to examine student's motivation towards learning Islamic studies. The purposes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…The learning methods used in learning can also affect students' motivation so that later it impacts the learning outcomes of these students (Ariyanti et al, 2018). Furthermore, research in Iraq concluded that a teacher's learning and teaching model would increase student interest in the lesson (Mustafa, 2018). In addition to learning strategies (Mugiyati et al, 2022;Saleha et al, 2022), learning motivation is an essential indicator of improving student learning outcomes (Novita & Rusdi, 2021;Nuha & Munawaroh, 2022;Putra, 2021).…”
Section: |mentioning
confidence: 99%
“…The learning methods used in learning can also affect students' motivation so that later it impacts the learning outcomes of these students (Ariyanti et al, 2018). Furthermore, research in Iraq concluded that a teacher's learning and teaching model would increase student interest in the lesson (Mustafa, 2018). In addition to learning strategies (Mugiyati et al, 2022;Saleha et al, 2022), learning motivation is an essential indicator of improving student learning outcomes (Novita & Rusdi, 2021;Nuha & Munawaroh, 2022;Putra, 2021).…”
Section: |mentioning
confidence: 99%